Faktor Yang Berhubungan Dengan Kinerja Perawat Dalam Menerapkan Model Praktik Keperawatan Profesional Terhadap Kepuasan Pasien Diruang Rawat Inap RS Marinir - Fanny Noviany Saputri; Dwi Rochyani; Tommy J. F Wowor (MAHESA : Malahayati Health Student Journal, 2022)
ABSTRACT The hospital is an integral part of a social and health organization with the function of providing complete services, curing disease, and preventing disease in the community. Nursing is an inseparable part of other health professions in providing health services to patients. The professional nursing practice model is an intervention strategy that has provided a framework of work that aims to support nurses in controlling all nursing actions so that they run. The performance of nurses is a measure of the quality of service in a hospital. Performance is influenced by individual variables, psychological variables, and organizational variables. Satisfaction is a feeling of disappointment or pleasure that a person feels after comparing the results of a product on perceived performance with his expectations. This study aims to determine the relationship between the performance of nurses in applying the model of professional nursing practice to patient satisfaction in the inpatient room at RS Mariner. This Chi-Square study used a cross-sectional design. The sample in this study amounted to 67 nurses and 67 patients in the Mariner Hospital inpatient room. The sampling technique used was the total sampling technique. The research instrument consisted of a questionnaire about the professional nursing practice model, a nurse performance questionnaire, and a patient satisfaction questionnaire. This questionnaire has been tested for validity and reliability with Cronbach's alpha coefficient of professional nursing practice 0.842, Cronbach's alpha of nurse performance 0.906, and Cronbach's alpha of patient satisfaction 0.956. Data were analyzed using a quantitative description. The results showed that there was a relationship between nurse performance (p-value = 0.004), which means p a value (0.05) with the professional nursing practice model (p-value = 0.009, which means p a value (0.05) on patient satisfaction. Nurse performance with a professional nursing practice model can provide satisfaction to patients Keywords: Nurse Performance, Professional Nursing Practice Model, Patient Satisfaction ABSTRAK Rumah sakit merupakan bagian integral dari suatu organisasi sosial dan Kesehatan dengan fungsi menyediakan pelayanan paripurna, penyembuha penyakit dan pencegahan penyakit pada masyarakat. Keperawatan adalah bagian yang tidak terpisahkan dari profesi Kesehatan lain di dalam memberikan pelayanan kesehatan kepada pasien. Model praktik keperawatan professional merupakan suatu strategi intervensi yang telah menyediakan suatu kerangka pekerjaan yang bertujuan untuk mendukung perawat dalam mengontrol semua Tindakan keperawatan agar berjalan. Kinerja perawat merupakan tolak ukur dari kualitas pelayanan suatu rumah sakit. Kinerja dipengaruhi oleh variabel individu, variabel psikologis dan variabel organisasi. Kepuasan adalah perasaan kecewa atau senang yang dirasakan seseorang setelah membandingkan antara hasil suatu produk atas persepsi kinerja dengan harapan-harapannya. Penelitian ini bertujuan untuk mengetahui hubungan antara kinerja perawat dalam menerapkan model praktik keperawatan professional terhadap kepuasan pasien di ruang rawat inap rs mariner. Penelitian Chi Square ini menggunakan rancangan cross sectional. Sampel dalam penelitian ini berjumlah 67 perawat dan 67 pasien di ruang rawat inap rs mariner. Teknik pengambilan sampel menggunakan teknik total sampling. Instrument penelitian terdiri dari kuesioner tentang model praktik keperawatan professional kuesioner kinerja perawat dan kuesioner kepuasan pasien. Kuesioner ini telah diuji validitas dan reliabilitas dengan nilai koefisien cronbach’s alpha model praktik keperawatan professional 0,842 cronbach’s alpha kinerja perawat 0,906 dan cronbach’s alpha kepuasan pasien 0,956. Data dianalisis menggunakan deskriptif kuantitatif. Hasil penelitian menunjukan bahwa ada hubungan antara kinerja perawat (p value = 0.004) yang berarti nilai p ≤ a (0.05)dengan model praktik keperawatan professional ( p value = 0.009 yang berarti nilai p ≤ a (0.05) terhadap kepuasan pasien. Kinerja perawat dengan model praktik keperawatan professional dapat memberikan kepuasan terhadap pasien. Kata Kunci: Kinerja Perawat, Model Praktik Keperawatan Profesional, Kepuasan Pasien